The caudolaterally inserted transposition flap and its variations for reconstruction of defects of the nasal ala - Felcht, Moritz (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Summary Closure of non-full-thickness defects of the nasal ala can be a surgical challenge. While there is a plethora of various reconstructive techniques, not all of them are easy to learn and carry out. Recently, the dermatosurgeon Andreas Lösler from the Department of Dermatology at the Hornheide Medical Center, Germany, developed and published the caudolaterally inserted transposition flap for the reconstruction of alar defects. Given its relative novelty, this technique, which is characterized by a very low complication rate, is still unknown to most dermatosurgeons and has not yet found its way into standard dermatosurgery textbooks. The present review describes the caudolaterally inserted transposition flap and two modifications thereof, which allow for the closure of large alar defects as well as defects of the alar crease. Comparisons are made to the two flaps most commonly employed for alar reconstruction, the bilobed flap and the cranially inserted nasolabial transposition flap (melolabial flap).
Gesehen am 07.11.2018